PENGARUH SENAM HAMIL TERHADAP TEKANAN DARAH PADA IBU HAMIL - Suraya, Sania Bela; Setyarini, Didien Ika; Rosmalawati, Ni Wayan Dwi; Apsari, Duhita Dyah (Malang Journal of Midwifery (MAJORY), 2025)
One of the changes in the physiology of pregnant women is changes in blood circulation. The most common circulatory system problem is hypertension. Pregnancy is one of the risk factors for high blood pressure or hypertension. In pregnancy there is an increase in sensitivity to vasopressor substances which leads to an increased risk of hypertension. Preecampsia is the most common hypertensive condition and is the second leading cause of maternal mortality in Indonesia. The purpose of the study was to analyze the effect of prenatal exercise on blood pressure in pregnant women at the Kraton Pasuruan Health Center. The research design used Quasi Experiment with one group pre test-post test design. The population amounted to 12 pregnant women using purposive sampling technique obtained a sample of 10 pregnant women. The research instrument used an observation sheet to measure blood pressure before and after prenatal exercise which was done once a week for 4 weeks. From the results of the Wilcoxon test, the p value = 0.005 (p < 0.05) that there is an effect of prenatal exercise on the mean blood pressure after prenatal exercise, blood pressure is lower than the mean before prenatal exercise. Prenatal exercise is a physical exercise that increases blood flow and dilates blood vessels so that it is likely to reduce blood pressure in pregnant women. Therefore, pregnant women are recommended to do prenatal exercises regularly.